The interaction between Entamoeba histolytica and enterobacteria shed light on an ancient antibacterial response. (14th May 2019) - Guillén, Nancy
Abstract: The amoeba parasite Entamoeba histolytica interacts with the microbiota within the intestine. Enterobacteria are the major source of energy for this parasite. Here, we highlight that the interplay between enterobacteria and E. histolytica is also important for parasite survival during inflammatory stresses and for the success of amoebic infection.